Key opinion leaders — a critical perspective - Scher, Jose U.; Schett, Georg (Nature Reviews Rheumatology, 2020)
Enormous progress has been made in the field of rheumatology in the past several decades, historically led by publicly funded academic innovators but in more recent times with much greater involvement of the pharmaceutical industry. This shift in resources has created a complex new model for reinvestment in the medical community in which the vast majority of private funds are redirected towards influencing the prescription behaviour of practitioners through ‘key opinion leaders’, with the main purpose of enhancing and perpetuating profit rather than innovation and critical thinking, and often at the expense of partnerships with scientists (that is, basic and translational researchers) and academic collaborations. This new episteme brings multiple opportunities to rethink approaches to sustaining long-term critical research in the field, ultimately maximizing the return on investment: scientific knowledge for the benefit of patients and society. Central to such strategies should be the rebalancing of academia–industry partnerships towards academic research and the involvement of ‘innovation and knowledge leaders’, rather than mostly key opinion leaders.
CRIS-Team Scopus Importer:2020-12-11